Instructive Guidelines for Developing Online EFL Courses - مدور, مصطفى (Revues faculté des lettres et des langues, 2018)
Abstract: Designing an online course is a two-façade project; it requires technical and pedagogical considerations to make the instruction comprehensive and applicable. Combining technology and pedagogy creates a fresh and innovative learning experience; however, a mere combination of the two without considering what an online course needs to integrate as components ends up in a disappointing fiasco. This paper draws course designers’ attention to the principles of planning, designing, managing and assessing an online course. It concludes that going online in teaching is initially a promising decision as it meets the expectations of the new generation of learners. Yet, this decision could not be promising as it initially suggested if the teacher does not consider such components as compelling content, manageable layout, applicable platform, and diverse course loggers. الملخص             يعتبر تصميم درس على الخط مشروعا ذا واجهتين: واجهة تقنية وأخرى بيداغوجية وذلك لضمان عملية تعليمية شاملة و قابلا للتطبيق. إن هذا الدمج يجعل من تعليم اللغة الانجليزية تجربة مبتكرة و جديدة ولكن مجرد نقل التعليم من إطاره التقليدي إلى إطار افتراضي بدون اعتبار المقومات اللازمة لذلك حتما ينتهي بفشل مخيب. لذلك فهذا المقال يسلط الضوء على الأسس اللازمة لتخطيط وتصميم درس على الخط بالإضافة إلى طرق تسييره و تقييمه. توصل هذا المقال إلى أن الاتجاه نحو الدروس على الخط يعتبر في بادئ الأمر قرارا واعدا لأنه يتماشى مع توقعات جيل التكنولوجيا ولكنه يجب أن يدعم بمعرفة شاملة حول عناصر الدرس على الخط و خاصة المحتوى اللغوي المناسب, البنية  و الأرضية الالكترونية الملائمة لطبيعة الدرس بالإضافة إلى اعتبار أساليب المتعلمين المتباينة .